I don’t understand how I feel: mediating role of impaired self-mentalizing in the relationship between childhood adversity and psychosis spectrum experiences - Nonweiler, Jacqueline; Torrecilla, Pilar; Kwapil, Thomas R.; Ballespí, Sergi; Barrantes-Vidal, Neus (Frontiers in Psychiatry, 2023)
Introduction Childhood adversity is associated with the severity of multiple dimensions of psychosis, but the mechanisms underpinning the close link between the two constructs is unclear. Mentalization may underlie this relationship, as impaired mentalizing is found in various stages of the psychosis continuum. Nonetheless, the differential roles of self- and other-mentalizing in psychosis are not well understood. Methods Parallel multiple mediation was conducted for the relationship between a diverse range of childhood adversity types, including intentional and nonintentional harm, and schizotypy (positive, negative, disorganized), psychotic-like experiences (PLE) and paranoia via self-mentalizing (attention to emotions and emotional clarity) and other-mentalizing in n = 1,156 nonclinically ascertained young adults. Results Significant parallel multiple mediation models were found for all psychotic outcomes except negative schizotypy. The associations between intentionally harmful childhood adversity and psychotic outcomes were significantly mediated by increased attention to emotions for most models and decreased emotional clarity for some models. No significant mediation was found for parental loss. Paternal abuse was only mediated by attention to emotions whereas the effects of maternal abuse were mediated by attention to emotions and emotional clarity. Other-mentalizing only showed mediating effects on one of thirty models tested. Conclusion Results highlight the mediating role of impaired self-mentalizing in the association between childhood adversity and psychosis. This is consistent with disturbances of self-concept and self-boundary characterizing, in particular, the positive dimension of psychosis. Maternal versus paternal figures may contribute differentially to the development of mentalizing. These results could inform future preventative interventions, focusing on the development and maintenance of self-mentalizing.